2010
DOI: 10.1051/0004-6361/201014409
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution imaging of Galactic massive stars with AstraLux

Abstract: Context. Massive stars have high-multiplicity fractions, and many of them have still undetected components, thus hampering the study of their properties. Aims. I study a sample of massive stars with high angular resolution to better characterize their multiplicity. Methods. I observed 138 fields that include at least one massive star with AstraLux, a lucky imaging camera at the 2.2 m Calar Alto telescope. I also used observations of 3 of those fields with ACS/HRC on HST to obtain complementary information and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 33 publications
(54 reference statements)
2
42
0
Order By: Relevance
“…3, but component B was clearly separated from A in the processed data in all cases (Aa and Ab components cannot be separated with lucky imaging). The first epoch was discussed by Maíz Apellániz (2010), where the reader is referred for further details on the data.…”
Section: Observationsmentioning
confidence: 99%
“…3, but component B was clearly separated from A in the processed data in all cases (Aa and Ab components cannot be separated with lucky imaging). The first epoch was discussed by Maíz Apellániz (2010), where the reader is referred for further details on the data.…”
Section: Observationsmentioning
confidence: 99%
“…(5) Lastly, stellar multiplicity seems to play a fundamental role in the context of massive stars, significantly affecting their evolution (e.g., Eldridge et al 2013). Several studies in the past years (e.g., Mason et al 2009;Maíz Apellániz 2010;Chini et al 2012;Sana et al 2013;Sota et al 2014;Aldoretta et al 2014) give direct evidence that at least half of the massive stars are found in multiple systems. Massive stars in close binary systems generally evolve differently from single stars.…”
Section: Introductionmentioning
confidence: 99%
“…This is in accord with a recent spectroscopic survey finding that among ∼240 southern Galactic O and WN stars more than 100 stars show radial velocity (RV) variations larger than 10 km s −1 (Barbá et al ). Recently, a high‐resolution imaging campaign of 138 fields containing at least one high‐mass star yielded a multiplicity fraction close to 50 per cent (Maíz‐Apellániz ). In summary, the spectroscopic binary frequency of high‐mass stars so far observed and reported in the literature is moderately high, while the visual binary fraction is low.…”
Section: Introductionmentioning
confidence: 99%